Prenatal features of ductus arteriosus‐related branch pulmonary stenosis in fetal pulmonary atresia. (4th August 2021) - Ngwezi, D. P.; McClean, M.; McBrien, A.; Eckersley, L.; Abeysekera, J.; Colen, T.; Hornberger, L. K.
ABSTRACT: Objective: Ductus arteriosus (DA)‐related branch pulmonary stenosis (PS), due to ductal tissue migration into the proximal pulmonary artery (PA) ipsilateral to the DA, is common in newborns with pulmonary atresia (PAtr) and contributes significantly to their mortality and morbidity. We sought to define fetal echocardiographic predictors of DA‐PS in PAtr. Methods: This was a study of all neonates diagnosed prenatally with PAtr and a DA‐dependent pulmonary circulation, with a DA that joined the underbelly of the arch, who had undergone surgical or catheter intervention in our hospital between 2009 and 2018. The postnatal echocardiograms and clinical records were reviewed to confirm the presence or absence of DA‐PS based on the need for angioplasty at initial intervention and/or development of proximal PA stenosis post intervention. Fetal echocardiograms were examined for the features of DA‐PS. Results: Of 53 fetuses with PAtr, 34 (64%) had analyzable images, including 20/34 (59%) with and 14/34 (41%) without DA‐PS. An inability to visualize the branch PAs in the same plane, largely associated with abnormal DA insertion into the ipsilateral PA (85% of cases), had sensitivity, specificity and positive (PPV) and negative (NPV) predictive values of 75%, 100%, 100% and 74%, respectively, for the prediction of postnatal DA‐PS. The mean branch PA posterior bifurcation angle was more obtuse in cases with DA‐PS compared to cases without DA‐PS (117° ± 17° vs 79° ± 17°, P < 0.001), and an angle of > 100°, the preoperative cut‐off observed previously in affected newborns, had a sensitivity, specificity, PPV and NPV of 88%, 79%, 82% and 85%, respectively. The receiver‐operating‐characteristics curve revealed an angle of ≥ 105° to have a sensitivity and specificity of 88% and 93%, respectively, for prenatal prediction of DA‐PS. The presence of one or both features (inability to image in the same plane and the posterior bifurcation angle of ≥ 105°) had a sensitivity, specificity, PPV and NPV of 100%, 93%, 95% and 100%, respectively. Conclusion: An inability to visualize the branch PAs in the same plane, associated with abnormal insertion of the DA in most cases, and/or the presence of a posterior PA bifurcation angle of ≥ 105° are predictive features of postnatal DA‐PS in fetuses with PAtr. © 2020 International Society of Ultrasound in Obstetrics and Gynecology.